2010
DOI: 10.1007/s00011-010-0199-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of chlorogenic acid on acute hepatotoxicity induced by lipopolysaccharide in mice

Abstract: Our data suggest that CGA has remarkable hepatoprotective effects on LPS-induced liver injury and that the possible mechanism is related to its anti-inflammatory action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 37 publications
6
65
0
5
Order By: Relevance
“…It has been reported that TNF-a and IL-6 are the key pro-inflammatory cytokines to trigger an inflammatory cascade involving massive apoptosis of hepatocytes and nephrocytes, and consequent damages of hepatic and renal functions (Mei & Zheng 2009;Sarkar & Fisher 2006;Xu et al 2010). TNF-a and IL-6 are critical players in liver and kidney damage (Nowak et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TNF-a and IL-6 are the key pro-inflammatory cytokines to trigger an inflammatory cascade involving massive apoptosis of hepatocytes and nephrocytes, and consequent damages of hepatic and renal functions (Mei & Zheng 2009;Sarkar & Fisher 2006;Xu et al 2010). TNF-a and IL-6 are critical players in liver and kidney damage (Nowak et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the important ingredients of green coffee beans (Bekedam et al 2008) and also in many kinds of fruits and vegetables such as apples, cherries, plums, berries, apricots, tomatoes, and potatoes (Heitman & Ingram 2014). Several recent studies have demonstrated that CGA exerts a variety of pharmacological effects, including antioxidative and anti-inflammatory effects (Xu et al 2010;Sato et al 2011). Previous research found that CGA protected mice against lipopolysaccharideinduced inflammatory responses in acute lung injury (Zhang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has also pointed out that the hepatotoxicity of 5-CQA can be markedly increased when the peroxidase/H 2 O 2 oxidation system was added to hepatocyte incubations (Moridani et al, 2001). Regardless of several research groups who have shown the antioxidative property of 5-CQA (Pari et al, 2010;Xu et al, 2010;Sato et al, 2011), the anti-and pro-oxidation properties of 5-CQA are not contradictory. The dose is critical with regards to the metabolic fate of the compound as well as metabolic switching and the route of administration.…”
Section: Xie Et Almentioning
confidence: 99%
“…Thereby, the lonicerae flos extract is further developed as a drug candidate currently undergoing a phase I trial (Korea Food and Drug Administration, Identifier HSP Injection_101 Version 2.00) for sepsis treatment. Moreover, CGA ameliorates LPS-induced acute hepatotoxicity in D-galactosamine (GalN)-sensitized mice (22). This liver injury is also known as an innate immunity-related disorder, but differs from LPS-induced systemic endotoxemia in that it involves a sudden hepatocellular apoptosis with minimal necrosis (23).…”
mentioning
confidence: 99%